Case Study : Application of Progressive Muscle Relaxation Methods in Third Trimester Pregnant to Reduce Fatigue During The Covid-19 Pandemic: Penerapan Metode Relaksasi Otot Progresif Pada Ibu Hamil Trimester Tiga Untuk Mengurangi Kelelahan Selama Pandemi Covid-19: Studi Kasus - Nurul Miftahul; Imami Nur Rachmawati (Politeknik Kesehatan Kemenkes RI Jakarta I, 2021)
Fatigue is the most common thing in third trimester pregnant women. Fatigue that occurs in third trimester pregnantwomen includes physiological and psychological aspects. Pregnancy during a pandemic is a new thing that challengingto pregnant women in social life. Pandemic also impact a social life of mother during the third trimester of pregnancy.The purpose of this paper is to analyze the implementation of nursing care in third trimester pregnant women whoexperience fatigue during a pandemic. Fatigue that occurs is often considered normal and a trigger factor for healthproblems of pregnant women and fetuses. One of an intervention to reduce fatigue in pregnant women is progressivemuscle relaxation. Progressive Muscle Relaxation (PMR) is a non-pharmacological action that focuses on relaxation ofthe mind and body that can reduce physiological and psychological fatigue in pregnant women. Provision of PMRintervention is given for 10 days. The results obtained were measured through pre and post intervention, there was adecrease in the level of fatigue by a mean difference of 4.3 (8.6%) as measured by the instrument MAF (MultidimentionalAssesment of Fatigue). Fatigue that previously disturbed activity to not interfere with daily activities. Based on that PMRintervention in third trimester pregnant women effectively reducing the level of fatigue so that pregnant women canmaintain their health status during a pandemic.